Exercise in humid versus dry heat : effects of pre- and mid-exercise cooling on endurance capacity - Tan, Isabelle Yu Zhen (Nanyang Technological University, 2021)
Ice slurry ingestion is an effective and practical strategy to enhance endurance performance in the heat. However, there are limited studies investigating its effect in high humidity environments and comparing between different humidity levels. Thus, this study aims to investigate the effects of pre- and mid-cooling with ICE in either humid or dry heat environments. Four males (age 27.5 ± 4.0 years) were recruited and assigned to four trials (A: ICE+Humid; B: CON+Humid; C: ICE+Dry; D: CON+Dry) in a randomized and counterbalanced order. Participants ingested 2 x 4g/kg bodyweight ICE (0°C) or CON (37°C) during 30-minutes of seated rest (pre-cooling) and 3 x 3.5g/kg bodyweight ICE/CON during 45-minutes of steady-state cycling at 50%VȮ2peak (mid-cooling) in a hot (34.7 ± 0.7°C) and either humid (81.5 ± 3.5%) or dry (36.5 ± 3.5%) environment followed by a time trial at 80%VȮ2peak. Core temperature (Tc), skin temperature (Tsk), heart rate (HR), rating of perceived exertion (RPE), thermal sensation (TS), and thermal comfort (TC) were recorded. Average time to exhaustion was longer with ICE ingestion (humid: +118.25s; dry: +94.25s). Mean Tc reduced by 0.55°C (humid) and 0.72°C (dry) after pre-cooling with ICE and remained lower than CON throughout exercise. During exercise, RPE and TS were lower with ICE by -2 and -0.9 (humid), and -1 and -0.5 (dry) respectively. HR, mean Tsk and TC showed no difference with ICE. Overall, the physiological measurements were lower in dry heat regardless of drink temperature. In conclusion, pre- and mid-cooling with ICE is an effective ergogenic aid to prolong exercise duration and reduce Tc during exercise in hot environments.